Genetic Detection of Quinolone Resistance in Haemophilus parainfluenzae: Mutations in the Quinolone Resistance-Determining Regions of gyrA and parC. Issue 1 (2010) - Law, Dennis KS; Shuel, Michelle; Bekal, Sadjia; Bryce, Elizabeth; Tsang, Raymond SW
Abstract : The quinolone resistance-determining regions of gyr A and par C of both quinolone-sensitive and quinolone-resistant Haemophilus parainfluenzae strains were amplified and sequenced. Similar to Haemophilus influenzae, resistance to quinolones in H parainfluenzae is associated with mutations in the quinolone resistance-determining regions of both gyr A and par C. The present study discusses the importance of this finding.